The Pengembangan Komik Digital Berorientasi Problem Based Learning (PBL) untuk Meningkatkan Literasi Sains Siswa Sekolah Dasar - Mutiaramses Mutiaramses; Yanti Fitria (Jurnal Penelitian Pendidikan IPA, 2022)
The integrated thematic learning process in elementary schools tends to be conventional and uses limited learning resources such as textbooks without being accompanied by learning media, so that students are dominantly bored and lazy to study. Students are given scientific literacy questions, the results obtained by students are still low. The research objective is to produce digital comics as an alternative technology-based learning media that can improve students' scientific literacy. The type of research chosen is R&D research with the ADDIE development model, namely Analyze, Design, Development, Implementation, and Evaluation. Research instruments in the form of questionnaires or questionnaires, tests, and documentation. The research design used was a pretest and posttest in the form of multiple-choice evaluation questions containing the domain of scientific literacy with a total of 18 questions for Indonesian subjects, 12 questions each for Mathematics and SBDP subjects. Comic validation involves five validators, each from a material, media design, and constructor expert. The results of the validity of comics obtained an average score of 89 (B) for the media, the average score of 89 (B) for the material, and the average construct was 92 (SB). Students' scientific literacy obtained an average score of 86.30 Indonesian (B) with a mastery percentage of 89%. Mathematics 85.00 (B) with 89% completeness percentage. The average SBDP score is 92.10 (SB) with a 100% completeness percentage. Thus, the development of PBL-oriented digital comics to improve students' scientific literacy is declared valid, practical, and effective